Uncovering the relationship between working memory and performance in the Jigsaw classroom - Eva Vives; Marco Bressan; Céline Poletti; Denis Caroti; Fabrizio Butera; Pascal Huguet; Isabelle Régner (PLoS ONE, 2025)
The Jigsaw classroom is a popular cooperative learning method based on resource interdependence, which requires students to work in small groups on complementary pieces of information, to achieve learning. However, Jigsaw classroom is characterized by contradictory findings and a lack of knowledge on its underlying cognitive mechanisms. The present study examined whether working memory capacity, a key executive function for academic achievement and learning, mediated or moderated the effects of Jigsaw classroom on individual performance. Undergraduate students (n ==  342) attending French University took part in this study (Mage ==  19.40, SD ==  1.21, 60% female). Students worked in small groups on a critical thinking reasoning task, either in the Jigsaw condition or in a cooperative (control) condition without resource interdependence. Working memory was assessed twice, before and during the group activities, by using a complex working memory span task. We analyzed students’ individual score to a quiz on logical fallacies. Multilevel analyses revealed that working memory capacity moderated—but did not mediate—the effect of the Jigsaw classroom. That is, Jigsaw enhanced performance for students with low working memory capacities. These findings offer insight into the potential cognitive mechanisms implied in the success of the Jigsaw method and provide new recommendations for educators on how to redeem the deficit of low working-memory-capacity students on performance.